Sound Alternations (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the concept of sound alternations in linguistics, focusing on the changes that occur in the phonetic or phonological form of words across different contexts. The discussion includes various types of sound alternations, their linguistic significance, and examples from different languages. Through this exploration, the article aims to provide a comprehensive understanding of how sound alternations contribute to the richness and complexity of language systems.